Barriers and facilitators to pulmonary rehabilitation in COPD: a mixed-methods systematic review - Hua Qin; Ping Jia; Qilin Yan; Xi Li; Yan Zhang; Hong Jiang; Hongmei Yang; Linzhang Li (BMC Pulmonary Medicine)
Abstract Objective This mixed-methods systematic review examines determinants influencing engagement in pulmonary rehabilitation (PR) among patients with chronic obstructive pulmonary disease (COPD) and synthesizes evidence to guide intervention strategies. Methods Following PRISMA guidelines, 29 studies (2006–2023) from eight databases were analyzed using the Joanna Briggs Institute (JBI) convergent integrated approach for data integration. The PRECEDE model categorized barriers into predisposing (psychological, health literacy), reinforcing (interpersonal dynamics), and enabling (structural) domains. Methodological quality was assessed with the Mixed Methods Appraisal Tool. Results Psychological barriers, such as anxiety and low health literacy, significantly diminished motivation for rehabilitation. Interpersonal challenges revealed insufficient healthcare provider competencies-such as inadequate clinical guidance and communication gaps-which undermined therapeutic alliances and patient adherence. Family support enhanced participation but risked dependency without structured education. Structural inequities, particularly urban-rural resource disparities and financial constraints, systematically excluded vulnerable populations. Persistent smoking emerged as a critical behavioral barrier, reflecting both physiological and self-care challenges. Facilitators included trust in healthcare providers, accessible urban rehabilitation resources, and personalized care plans. Conclusion PR participation is governed by interacting psychological, interpersonal and structural factors that shift with care context. A six-domain implementation schema (mental-health screening, flexible access, tele-rehabilitation plus caregiver toolkits, clinician up-skilling, peer reinforcement and targeted economic support) provides actionable leverage to lessen barriers and strengthen facilitators. Empathic, two-way communication among professionals, patients and families remains pivotal to converting exercise prescriptions into durable self-management. Future research should test the effectiveness and cost-utility of this integrated package across settings and further refine digital tools for tailoring programme intensity and follow-up.